Purification and characterization of Shiga toxin 2f, an immunologically unrelated subtype of Shiga toxin 2. - Craig Skinner; Stephanie McMahon; Reuven Rasooly; John Mark Carter; Xiaohua He (PLoS ONE, 2013)
BACKGROUND: Shiga-like toxin 2 (Stx2) is one of the most important virulence factors in enterohaemorrhagic Escherichia coli (E. coli) strains such as O157H7. Subtypes of Stx2 are diverse with respect to their sequence, toxicity, and distribution. The most diverse Stx2 subtype, Stx2f, is difficult to detect immunologically, but is becoming more frequently associated with human illness. METHODS AND FINDINGS: A purification regimen was developed for the purification of Stx2f involving cation exchange, hydrophobic interaction, anion exchange, and gel filtration. The molecular weight of Stx2f B-subunit was approximately 5 kDa, which appeared significantly smaller than that of Stx2a (6 kDa) on a SDS-PAGE gel, although the size of the A subunit was similar to Stx2a (30 kDa). Stx2f was shown to be active in both cell-free and cell-based assays. The 50% cytotoxic dose in Vero cells was 3.4 or 1.7 pg (depending on the assay conditions), about 3-5 times higher than the archetypical Stx2a, while the activity of Stx2f and Stx2a in a cell-free rabbit reticulocyte system was similar. Stx2f bound to both globotriose-lipopolysaccharide (Gb3-LPS) and globotetraose-LPS (Gb4-LPS, mimics for globotriaosylceramide and globotetraosylceramide, respectively), but its ability to bind Gb4-LPS was much stronger than Stx2a. Stx2f was also much more stable at low pH and high temperature compared to Stx2a, suggesting the toxin itself may survive harsher food preparation practices. CONCLUSIONS: Here, we detail the purification, biochemical properties, and toxicity of Stx2f, from an E. coli strain isolated from a feral pigeon. Information obtained in this study will be valuable for characterizing Stx2f and explaining the differences of Stx2a and Stx2f in host specificity and cytotoxicity.